SPE Annual Technical Conference and Exhibition 1990
DOI: 10.2118/20653-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Production Optimization System for Western Prudhoe Bay Field, Alaska

Abstract: For almost a decade the Prudhoe Bay field on the North Slope of Alaska has produced at a yearly average offtake rate of 1.5 million stock tank barrels of oil per day. As the reservoir depletes and field gas-oil ratios (GaRs) increase, gas handling constraints make it difficult to achieve oil rate targets. The Western Production Optimization Model (WPOM) was developed by BPX to deliver an offtake strategy that maximizes oil rate while minimizing processed gas. The model is based on the "incremental GaR" concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It was determined optimal allocation of lift-gas to wells subject to multiple gas constraints at Kuparuk River field (Stoisits et al, 1992(Stoisits et al, , 1999). Short-term production optimization WPOM was applied in the Prudhoe Bay field of the North-Slope of Alaska, and to long-term reservoir development studies for two fields in the Gulf of Mexico was applied and its result demonstrated the effectiveness of the approach (Barnes et al, 1990, Stoisits et al, 1999, Wang, 2003. Continuous gas-lift method was employed in offshore operations (Clegg et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was determined optimal allocation of lift-gas to wells subject to multiple gas constraints at Kuparuk River field (Stoisits et al, 1992(Stoisits et al, , 1999). Short-term production optimization WPOM was applied in the Prudhoe Bay field of the North-Slope of Alaska, and to long-term reservoir development studies for two fields in the Gulf of Mexico was applied and its result demonstrated the effectiveness of the approach (Barnes et al, 1990, Stoisits et al, 1999, Wang, 2003. Continuous gas-lift method was employed in offshore operations (Clegg et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…It was presented the Western Production Optimization Model (WPOM) for the Prudhoe Bay field. This model maximizes oil production while minimizing the need for gas processing that allocates the oil rate and gas rate to surface facilities and wells based on the "incremental gas oil ratio (GOR)" concept (Barnes et al, 1990, Wang, 2002. It has been reported that (Litvak et al 1997) an integrated reservoir and gathering system model of the Prudhoe Bay field, and employed various heuristic methods to optimize well connections to manifolds.…”
Section: Introductionmentioning
confidence: 99%
“…A way of handling a gas compression constrained field under gas coning conditions was proposed by Barnes et al [7]. The method is able to handle wells where the incremental gas oil ratio (IGOR) is monotonically increasing with the oil rate.…”
Section: Technology and Reference Casesmentioning
confidence: 99%
“…These can be classified into three categories: (1) sensitivity analysis using simulation tools, (2) heuristic methods, and (3) mathematical programming methods. For example, Barnes et al 4 and Stoisits et al 5 have studied the problem of allocating limited amount of available gas-to-gas lift wells using heuristic rules, which have been developed based on single well analysis. Martinez et al 6 and Buitrago et al 7 applied various mathematical programming techniques such as quasi-Newton and genetic algorithms.…”
Section: Introductionmentioning
confidence: 99%